2021
DOI: 10.1177/1535370220983243
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear translocation of β-catenin induced by E-cadherin endocytosis causes recurrent erosion of diabetic cornea

Abstract: Recurrent epithelial erosion and refractory corneal ulcer are the clinical features of diabetic keratopathy (DK), which eventually lead to corneal scar and visual disturbance. In this study, we sought to determine the abnormalities of cell junction in diabetic corneal epithelial cells and the effect of high glucose on the β-catenin/E-cadherin complex. Corneal histology showed that corneal epithelial cells of high glucose mice were loosely arranged, and the immunohistochemistry showed that the expression of E-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Consequently, our observations implied that the MICAL2mediated downregulation of E-cadherin protein levels may be the primary inducer of β-catenin nuclear translocation. This decrease in E-cadherin content was consistent with the results of Ma et al [32], who showed that high glucose levels induced the degradation of E-cadherin in corneal epithelial cells, subsequently leading to reduced β-catenin/E-cadherin complex formation and the promotion of β-catenin nuclear translocation. That Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, our observations implied that the MICAL2mediated downregulation of E-cadherin protein levels may be the primary inducer of β-catenin nuclear translocation. This decrease in E-cadherin content was consistent with the results of Ma et al [32], who showed that high glucose levels induced the degradation of E-cadherin in corneal epithelial cells, subsequently leading to reduced β-catenin/E-cadherin complex formation and the promotion of β-catenin nuclear translocation. That Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The maintenance of appropriate cell adhesion is crucial for cell migration and wound healing. A previous study reported that the E-cadherin/β-catenin complex is involved in the adhesion of corneal epithelial cells and high glucose induced decreased expression of E-cadherin and β-catenin in mouse corneal epithelial cells, as well as reducing the formation of β-catenin/E-cadherin complex ( 20 ). β-catenin plays an essential role in the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of recurrent erosions in animal models have allowed us to gain insight into how erosions form and to develop improved treatments [6][7][8][9][10][11]. While the mouse cornea lacks a thick Bowman's layer under its epithelial basement membrane (EBM), studies using the mouse cornea have, nevertheless, shown how important the interaction between corneal epithelial cells and the basement membrane is in re-establishing homeostasis after corneal injury [6,7].…”
Section: Introductionmentioning
confidence: 99%